Model Pembelajaran Learning Cycle 5E Terhadap Keterampilan Critical Thinking Matematis Materi Fungsi Ditinjau dari Kemampuan Awal Siswa - Susanti, Tri; Jamilah, Jamilah; Ardiawan, Yadi (Lembaga Intelektual Muda (LIM) Maluku, 2024)
This research aims to improve students' critical thinking or critical thinking skills which are divided into three levels, namely students who have high level, medium level, and low-level critical thinking through the application of the Learning Cycle 5E learning model in class X. This research is quasi-experimental research namely the development of true experimental design with Nonequievalent control group design research design through Posttest-Only Control Design carried out at Sukake 1 Public High School. The sample selected used Cluster random sampling, namely class X MIA 1 which was used as the experimental class. Data collection was carried out by trial at SMA Negeri 2 Menyuke followed by research school at SMA Negeri 1 Menyuke using the Learning Cycle 5E learning model and post-test final test to determine students' mathematical critical thinking skills at high, medium, and low levels, interviews to find out student responses regarding the results of the answers. The t-test results for both normal and homogeneous distributions obtained a significance value (2-tailed) = 0.031 < 0.05 with the decision H_1 being accepted. It was proven that there was a significant difference between the learning outcomes in the control class and the learning outcomes of students in the experimental class. Descriptively, students show improvement. Students also experienced quite good improvement. So, it can be concluded that the Learning Cycle 5E learning model provides an increase in critical thinking skills